Decrease of Antimicrobial Resistance through Polyelectrolyte-Coated Nanoliposomes Loaded with β-Lactam Drug - Lina M. Arévalo; Cristhian J. Yarce; José Oñate-Garzón; Constain H. Salamanca (MDPI AG, 2018)
Currently, one of the greatest health challenges worldwide is the resistance to antibiotic drugs, which has led to the pursuit of new alternatives for the recovery of biological activity, where the use of different types of nano-systems has shown an interesting potential. In this study, we evaluated the antibiotic activity of a model drug (ampicillin) encapsulated within coated-nanoliposomes on strains of Staphylococcus aureus with different antibiotic-resistance degrees. Hence, liposomes were elaborated by the ethanol injection method and were coated with a cationic polymer (Eudragit E-100) through the layer-by-layer process. Liposome characterization, such as size, polydispersity, zeta potential, and encapsulation efficiency were determined using dynamic light scattering and ultrafiltration/centrifugation techniques. Although biological activity was evaluated using three ATCC strains of S. aureus corresponding to ATCC 25923 (sensitive), ATCC 29213 (resistant) and ATCC 43300 (very resistant). The results showed changes in size (from ~150 to 220 nm), polydispersity (from 0.20 to 0.45) and zeta potential (from −37 to +45 mV) for the coating process. In contrast, encapsulation efficiency of approximately 70% and an increase in antibiotic activity of 4 and 18 times more on those S. aureus-resistant strains have been observed.